The effects of an innovative reflexive self-talk intervention on organic self-talk and self-regulatory skills in young elite athletes - Jovanovic, J. (University of Thessaly, 2022)
The present study followed the experiences of four national representative athletes (17 to 19 years old) who were involved in the reflexive self-talk intervention. The participants underwent 6-8 sessions in which their goal-directed self-talk and use of mental skills in psychologically challenging situations were discussed. Moreover, the psychologist who conducted the intervention combined a Socratic questioning approach and scaffolding in order to facilitate the athlete`s awareness of their self-talk in challenging situations and to introduce them the mental skills and their utility in such situations. Data was collected from multiple sources: psychologist, athletes, and third parties (e.g., coach). Moreover, supplementary to the interviews, the study adopted the sport-psych mapping in order to gather the data about the intervention effects on the performance-related variables in athletes. All the athletes completed the intervention and positively rated the intervention in overall. Further, all athletes reported an increase in their awareness and positive changes in performance-related variables (e.g., motivation, concentration). Additionally, all athletes reported increased usage of mental skills and underlined the benefits for their performance. The study also presented the updated mechanism of the reflexive self-talk intervention effects. Moreover, the present study highlighted the needs of the young athletes and the challenges for a psychologist when conducting such an intervention. Accordingly, the present study paved the way for future studies on reflexive self-talk intervention.